The impact of rare diseases on the quality of life in paediatric patients: current status - Dumbuya, John Sieh; Zeng, Cizheng; Deng, Lin; Li, Yuanglong; Chen, Xiuling; Ahmad, Bashir; Lu, Jun (Frontiers in Public Health, 2025)
Rare diseases, also known as orphan diseases, are a group of disorders that affect a small percentage of the population. Despite individually affecting a small number of people, collectively, they impact millions worldwide. This is particularly significant in paediatric patients, highlighting the global scale of the issue. This review delves into the exact prevalence of rare diseases among children and adolescents and their diverse impact on the quality of life of patients and their families. The review sheds light on the complex interplay of genetic and environmental factors contributing to these conditions and the diagnostic challenges and delays often encountered in identifying and categorising these diseases. It is noted that although there have been significant strides in the field of genomic medicine and the development of orphan drugs, effective treatments remain limited. This necessitates a comprehensive, multidisciplinary approach to management involving various specialities working closely together to provide holistic care. Furthermore, the review addresses the psychosocial and economic burdens faced by families with paediatric patients suffering from rare diseases, highlighting the urgent need for enhanced support mechanisms. Recent technological and therapeutic advancements, including genomic sequencing and personalized medicine, offer promising avenues for improving patient outcomes. Additionally, the review underscores the role of policy and advocacy in advancing research, ensuring healthcare access, and supporting affected families. It emphasises the importance of increased awareness, education, and collaboration among healthcare providers, researchers, policymakers, and patient advocacy groups. It stresses the pivotal role each group plays in improving the diagnosis, treatment, and overall quality of life for paediatric patients with rare diseases.